The Physical Geographies Dimensions in Teaching Practice: A Case Study of Five EFL Pre-service Teachers - Riski, Riski; Hartono, Rudi; Sakhiyya, Zulfa (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2024)
This qualitative case study included five EFL pre-service teachers who had completed 45 days of FTP at one of senior high schools in Kendari, Southeast Sulawesi. This study aimed to investigate the physical geographies of pre-service teachers while they conducted their teaching practice. Reflective journals and interviews are data collection instruments constructed based on Hargreaves' emotional geographies theory to comprehend the emotions that arise after completing their field teaching experience in 45 days. This study discovered that the participants had both positive and negative feelings during their field teaching practicum (FTP) in physical geography aspects. As part of their physical geography dimensions, all participants maintained tremendous relationships with their students, colleagues, and mentor teachers at placement schools. As a result, their emotional geographies could involve the teacher's professional and cognitive abilities, which impact their field teaching practice.